Caliphate and Kingship in a Fifteenth-Century Literary History of Muslim Leadership and Pilgrimage al-Ḏahab al-masbūk fī ḏikr man ḥaǧǧa min al-ḫulafāʾ wa-l-mulūk. Critical Edition, Annotated Translation, and Study - Van Steenbergen, Jo (Bibliotheca Maqriziana, 2016)
In Caliphate and Kingship Jo Van Steenbergen presents a revisionist cultural biography, a critical edition and an annotated translation of al-Ḏahab al-Masbūk, a summary history of the ḥağğ and Muslim rule by Egypt's leading historian al-Maqrīzī (d. 1442 CE). Readership: All interested in the history of the ḥağğ, in Muslim intellectual history and political theory, in premodern Arabic literature, and in medieval and Mamluk political and socio-cultural history